Analysis and Optimization Design of U-Shaped Ironless Permanent Magnet Linear Synchronous Motor - Zhang, Longqi; Zhao, Lei; Li, Shihao (International Journal of Mechanical and Electrical Engineering, 2024)
The working speed of the U-shaped ironless permanent magnet linear synchronous motor is determined by the frequency and pole pitch. When the motor’s working speed is required to be constant, different combinations of frequency and pole pitch can be chosen. This article mainly discusses the influence of the pole pitch on the motor performance when other parameters are kept constant. First, the magnetic field of the motor permanent magnet is analyzed using the equivalent magnetizing current method to discuss the relationship between the pole pitch and the motor air gap magnetic field. Then, the finite element method is used to analyze the influence of the pole pitch on the motor air gap magnetic field, transverse edge effect, and electromagnetic thrust considering the saturation effect of the magnetic yoke. The research shows that under the conditions of constant motor basic structural parameters and speed, and the same amount of permanent magnet material, both the air gap magnetic density and the motor thrust line density have maximum values as the pole pitch changes. The research results have certain guiding significance for the design of this type of motor.